Illuminating the dynamic rare biosphere of the Greenland Ice Sheet's Dark Zone. Issue 12 (7th November 2019) - Gokul, Jarishma K; Cameron, Karen A; Irvine-Fynn, Tristram D L; Cook, Joseph M; Hubbard, Alun; Stibal, Marek; Hegarty, Matt; Mur, Luis A J; Edwards, Arwyn
ABSTRACT: Greenland's Dark Zone is the largest contiguous region of bare terrestrial ice in the Northern Hemisphere and microbial processes play an important role in driving its darkening and thereby amplifying melt and runoff from the ice sheet. However, the dynamics of these microbiota have not been fully identified. Here, we present joint 16S rRNA gene and 16S rRNA (cDNA) comparison of input (snow), storage (cryoconite) and output (supraglacial stream water) habitats across the Dark Zone over the melt season. We reveal that all three Dark Zone communities have a preponderance of rare taxa exhibiting high protein synthesis potential (PSP). Furthermore, taxa with high PSP represent highly connected 'bottlenecks' within community structure, consistent with their roles as metabolic hubs. Finally, low abundance-high PSP taxa affiliated with Methylobacterium within snow and stream water suggest a novel role for Methylobacterium in the carbon cycle of Greenlandic snowpacks, and importantly, the export of potentially active methylotrophs to the bed of the Greenland Ice Sheet. By comparing the dynamics of bulk and potentially active microbiota in the Dark Zone of the Greenland Ice Sheet, we provide novel insights into the mechanisms and impacts of the microbial colonization of this critical region of our melting planet. Abstract : Rare microbes seem surprisingly busy on the surface of the Greenland Ice Sheet.